2012
DOI: 10.1021/es204540z
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of Silver Nanoparticle Coating on the Nitrification Potential of Nitrosomonas europaea

Abstract: Silver nanoparticles (AgNPs) are increasingly used as bacteriostatic agents to prevent microbial growth. AgNPs are manufactured with a variety of coatings, and their potential impacts on wastewater treatment in general are poorly understood. In the present study, Nitrosomonas europaea, a model ammonia oxidizing bacterium, was exposed to AgNPs with citrate, gum arabic (GA), and polyvinylpyrrolidone (PVP). GA and citrate AgNPs inhibited nitrification most strongly (67.9 ± 3.6% and 91.4 ± 0.2%, respectively at 2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
106
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 120 publications
(111 citation statements)
references
References 64 publications
4
106
1
Order By: Relevance
“…These results suggest that the water column CO 2 , DOC, and DO concentrations were not the primary drivers of methane concentrations. We therefore speculate that the patterns in methane could have been the result of several different mechanisms: a direct effect of Ag on sensitive membrane bound methane monoxygenase enzymes used by the microbes that metabolize methane; 18 an indirect effect of Ag on methanotrophs mediated by sediment dissolved oxygen and substrate concentrations; or the release of dissolved CH 4 from plant biomass. 40 Through our use of a mixed community of organisms in realistic environmental media and field conditions, our attempt to understand the impacts of nanoparticles on ecosystems led to surprising conclusions.…”
Section: ■ Discussionmentioning
confidence: 99%
“…These results suggest that the water column CO 2 , DOC, and DO concentrations were not the primary drivers of methane concentrations. We therefore speculate that the patterns in methane could have been the result of several different mechanisms: a direct effect of Ag on sensitive membrane bound methane monoxygenase enzymes used by the microbes that metabolize methane; 18 an indirect effect of Ag on methanotrophs mediated by sediment dissolved oxygen and substrate concentrations; or the release of dissolved CH 4 from plant biomass. 40 Through our use of a mixed community of organisms in realistic environmental media and field conditions, our attempt to understand the impacts of nanoparticles on ecosystems led to surprising conclusions.…”
Section: ■ Discussionmentioning
confidence: 99%
“…These concentrations were chosen on the basis of our previous study, which showed that the effects of AgNPs on the model wastewater ammonium oxidizing bacterium (AOB), Nitrosomonas europaea, became apparent around 2 ppm total Ag concentration. 10 Table 1 displays the chronology of Ag addition to the SBRs. Ag was initially added in pulses at 0.2 ppm followed by a continuous addition.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…Also, a similar survey has been conducted by Aranout et al [87]. They examined the effect of three types of coatings [gum arabicum (GA), acid citric and PVP] on Table 1.…”
Section: Types Of Nps Coatingsmentioning
confidence: 96%